ETOS KERJA PADA PENGRAJIN PAYUNG DI JUWIRING, KLATEN - Trisni Utami; Mahendra Wijaya (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This article in order to make formulation development centers in the umbrella industry Juwiring, Klaten. Beside that,this article describe to determine the potential production and marketing, the method used is the Baseline Research in order to identify the umbrella craftsmen work ethic. This is achieved through the identifiation of the production process: preparation of raw materials, forming and fiishing products, until the craft industry marketing umbrella. Second, by conducting a structured FGD industry centers on the development of an umbrella in Juwiring Work Ethics in the umbrella industry Juwiring high enough. This can be seen from the hours of work that are not familiar with the starting time of dawn until the evening before bed. Even when there is an order-melting craftsmen until late into the night with the involvement of all members of the family labor. Regerasi umbrella industry in Juwiring less able to run smoothly because most of the craftsmen elderly and young workers are not interested to continue business as pengajin umbrella. They prefer to work as an employee or employees